What Is the Difference Between Laboratory-Scale and Pilot-Scale Grape-Based Products for Older Adults with Chewing Difficulties? - Ye-Jun Kim; Ji-Hye Ryu; Jin-Young Lee; Yong-Suk Kim; Dasol Kim; Yongseok Kwon (Foods)
This study was conducted to develop a grape product that can facilitate fruit intake for elderly people with chewing difficulties. In addition, the possibility of field application for future prototype production was investigated by comparing laboratory-scale (lab-scale) and pilot-scale production. The stages (stage 1: able to eat with teeth, stage 2: able to eat with gums, stage 3: able to eat with tongue) of the products were determined according to the Korean Industrial Standards for Seniors Friendly Foods (KS H 4897), and the physicochemical composition was measured according to the general test method of the Food Code. The results of this study showed that when comparing the lab scale and pilot scale in stage 1, the hardness of the pilot scale was significantly increased (p < 0.05). Conversely, both hardness in stages 2 and 3 and viscosity in stage 3 showed a significant decrease in the pilot scale compared to the lab scale (p < 0.05). In addition, pH and sugar acidity were significantly different between the two scales in all stages (p < 0.05). These results confirmed the feasibility of developing customized grape products for the elderly with chewing difficulties, and the differences in physicochemical properties between lab-scale and pilot-scale production confirmed the importance of maintaining product quality during scaled-up production. These results can serve as a basis for developing foods for the elderly that require continuous development, and are expected to contribute to improving the dietary habits and quality of life of the elderly with chewing difficulties.